Enhancing the efficacy of cisplatin in ovarian cancer treatment - could arsenic have a role - Helm C William; States J Christopher (BMC, 2009)
Abstract Ovarian cancer affects more than 200,000 women each year around the world. Most women are not diagnosed until the disease has already metastasized from the ovaries with a resultant poor prognosis. Ovarian cancer is associated with an overall 5 year survival of little more than 50%. The mainstay of front-line therapy is cytoreductive surgery followed by chemotherapy. Traditionally, this has been by the intravenous route only but there is more interest in the delivery of intraperitoneal chemotherapy utilizing the pharmaco-therapeutic advantage of the peritoneal barrier. Despite three large, randomized clinical trials comparing intravenous with intraperitoneal chemotherapy showing improved outcomes for those receiving at least part of their chemotherapy by the intraperitoneal route. Cisplatin has been the most active drug for the treatment of ovarian cancer for the last 4 decades and the prognosis for women with ovarian cancer can be defined by the tumor response to cisplatin. Those whose tumors are innately platinum-resistant at the time of initial treatment have a very poor prognosis. Although the majority of patients with ovarian cancer respond to front-line platinum combination chemotherapy the majority will develop disease that becomes resistant to cisplatin and will ultimately succumb to the disease. Improving the efficacy of cisplatin could have a major impact in the fight against this disease. Arsenite is an exciting agent that not only has inherent single-agent tumoricidal activity against ovarian cancer cell lines but also multiple biochemical interactions that may enhance the cytotoxicity of cisplatin including inhibition of deoxyribose nucleic acid (DNA) repair. In vitro studies suggest that arsenite may enhance the activity of cisplatin in other cell types. Arsenic trioxide is already used clinically to treat acute promyelocytic leukemia demonstrating its safety profile. Further research in ovarian cancer is warranted to define its possible role in this disease.